Analisis Faktor Resiko Sebagai Upaya Pencegahan terhadap Kejadian Kasus Infeksi Saluran Kemih - Ramadhan, Cahya; Astuti, Dwi; Widyastuti, Riana; Sulistyorini, Mufita (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
Urinary tract infection (UTI) is a collective term that describes infections involving any part of the urinary tract, namely the kidneys, ureters, bladder and urethra. UTIs can affect patients of all ages from newborns to adults and the elderly. In general, women experience UTI episodes more often than men, this is because women's urethra is shorter than men's. However, neonatal UTIs are more prevalent in male infants (2.7%) who do not undergo circumcision than female infants (0.7%). This research uses a literature study method through several national and international journals obtained from 31 reference sources through searches on PubMed, Science Direct, ResearchGate, and Google Scholar that have been published in the last 5 years. The results of the review show that there are several risk factors that can trigger UTIs such as age, type of abnormality, genetics, gender, behavioral factors, and catheter use. The discovery of several factors that play a role in the occurrence of UTIs. This is used to help patients to know what risk factors must be controlled so that they are more aware of the incidence of UTI cases.